1990
DOI: 10.1111/j.1469-8749.1990.tb08103.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Test of the Quality of Motor Function of Children With Cerebral Palsy: Preliminary Study

Abstract: SUMMARY An objective test of motor function would enable better evaluation of various treatment programmes for children with cerebral palsy. The use of tri‐axial accelerometry was investigated in 36 children with cerebral palsy and in 53 children without disabilities. Variables discriminated well between able‐bodied and disabled children, and there was a high level of retest reliability. The technique requires further development, but shows promise of providing the ability to gather objective data about the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The Melbourne Assessment was developed and designed by two occupational therapists and a paediatrician, following extensive investigation of techniques for objectively measuring upper-limb movement in children with CP (Reddihough et al 1987(Reddihough et al , 1990(Reddihough et al , 1991Bach et al 1994). The Melbourne Assessment has three purposes as detailed in the manual.…”
Section: Psychometric Properties Of the Melbourne Assessmentmentioning
confidence: 99%
“…The Melbourne Assessment was developed and designed by two occupational therapists and a paediatrician, following extensive investigation of techniques for objectively measuring upper-limb movement in children with CP (Reddihough et al 1987(Reddihough et al , 1990(Reddihough et al , 1991Bach et al 1994). The Melbourne Assessment has three purposes as detailed in the manual.…”
Section: Psychometric Properties Of the Melbourne Assessmentmentioning
confidence: 99%
“…Previous investigations have demonstrated that the accelerometer can distinguish between normal children and children with movement disorders (Reddihough et al 1990). However, the sensitivity of the technique to finer differences in movement quality has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past four years efforts have been made by our group to develop an objective test, based on accelerometry, which might be sensitive enough to detect subtle changes in the quality of motor function of children with cerebral palsy. Initially a uni-axial accelerometor was used (Reddihough et al 1987), but in later investigations a tri-axial accelerometer was used to test unconstrained movement patterns (Reddihough et al 1990). These investigations showed that particular characteristics of the acceleration power spectrum had good retest reliability and discriminated between able-bodied and disabled children.…”
Section: Dinah Reddihough Tim Bach Greg Burgess Lin Oke Irene Hudsonmentioning
confidence: 99%
See 1 more Smart Citation
“…For test-retest reliability, the MHC, Quality of Upper Extremities Skills Test (QUEST), [28][29][30][31][32][33] UERS, Peabody Developmental Motor Scales-2-Fine Motor abilities (PDMS-2 FM), 41 VOAA-DDD-R, ABILHANDKids, 50 Münchner ADL-Fragebogen (M-ADL), 52 the PMAL "how often" scale, 53 and the Shriners Hospital for Children CP Computer-Adapted Testing battery-Upper Extremities 49 showed limited positive evidence. All other assessments (House-Classification, 21 Modified Ashworth Scale [MAS], [18][19][20] Mowery Classification, 21 47 and Accelerometry [25][26][27] ) were found to have unknown, conflicting, or negative levels of evidence for reliability (Table 2).…”
Section: Reliabilitymentioning
confidence: 99%